2004
DOI: 10.1074/jbc.m313853200
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Protein S-Nitrosylation

Abstract: The biological effects of nitric oxide (NO) are in significant part mediated through S-nitrosylation of cysteine thiol. Work on model thiol substrates has raised the idea that molecular oxygen (O 2 ) is required for Snitrosylation by NO; however, the relevance of this mechanism at the low physiological pO 2 of tissues is unclear. Here we have used a proteomic approach to study S-nitrosylation reactions in situ. We identify endogenously S-nitrosylated proteins in subcellular organelles, including dihydrolipoami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
105
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 67 publications
4
105
1
2
Order By: Relevance
“…These new thiols are then marked by introduction of a mixed-disulfide bond with a biotin-tagging reagent, captured on immobilized avidin, and selectively released from avidin by reduction of the disulfide linker. Several laboratories have used the biotin-switch method in combination with 1D or 2D PAGE and in-gel trypsinolysis for identification of SNO proteins by mass spectrometry (10)(11)(12)(13)(14). To extend the capability of this approach, we introduced a proteolytic digestion step before avidin capture.…”
Section: Snosid a Proteomic Methods For Identification Of Cysteine S-mentioning
confidence: 99%
“…These new thiols are then marked by introduction of a mixed-disulfide bond with a biotin-tagging reagent, captured on immobilized avidin, and selectively released from avidin by reduction of the disulfide linker. Several laboratories have used the biotin-switch method in combination with 1D or 2D PAGE and in-gel trypsinolysis for identification of SNO proteins by mass spectrometry (10)(11)(12)(13)(14). To extend the capability of this approach, we introduced a proteolytic digestion step before avidin capture.…”
Section: Snosid a Proteomic Methods For Identification Of Cysteine S-mentioning
confidence: 99%
“…For instance, DLDH was found to be modified by 4-hydroxynonenal (HNE) in the ventilatory muscles of rats challenged by lipopolysaccharide (Hussain, et al, 2006), and found to be nitrosylated in rat liver (Foster and Stamler, 2004) and in Mycobacterium tuberculosis (Rhee, et al, 2005). Because DLDH activity was not measured in these studies, it is not yet known whether or not the HNE modification or nitrosylation had any significant inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons why S-nitrosylation may be an important mitochondrial regulatory mechanism. For example, mitochondria contain sizeable pools of thiols and transition metals, all of which are known to modulate nitrosothiol (SNO) biochemistry (Foster and Stamler, 2004). In addition, mitochondria are highly membranous and accumulate lipophilic molecules such as NO.…”
mentioning
confidence: 99%
“…Furthermore, NO activates mitogen-activated protein kinases in different plant species during stress signaling (Nakagami et al, 2005). However, direct biological activity of NO arises from chemical reactions between proteins and NO itself (Foster and Stamler, 2004;Dahm et al, 2006). S-Nitrosylation is a labile posttranslational modification with a half-life of seconds to a few minutes and represents a very sensitive mechanism for regulating cellular processes (Hess et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation